Psychometric evaluation of the Holden Communication Scale (HCS) for persons with dementia - Strøm, Benedicte Sørensen (BMJ Open, 2016)
OBJECTIVE: To investigate the psychometric properties of the Holden Communication Scale (HCS) and the association between scores on HCS and cognitive function among persons with dementia. METHOD: Internal consistency was assessed by the Cronbach's α coefficient and inter-item correlations. Test-retest was carried out to test the instrument's stability. An exploratory factor analysis with the principal components extraction method and oblimin rotation was performed to evaluate construct validity. Pearson's correlation coefficients were calculated to explore associations between the scores on the HCS and cognitive function. RESULTS: A total of 128 persons with moderate-to-severe cognitive impairment (mean Mini-Mental State Examination (MMSE) score 8.9 (SD 7.0)) participated. The mean age was 85.2 (SD 7.2) and 101 of the participants were women. The Cronbach's α of the HCS was 0.94 and test-retest reliability was r=0.71. The corrected item-total correlation ranged from 0.63 to 0.79 and factor analysis showed a 1-factor structure of the HCS, which explained 63% of the variance. However, a forced 3-factor structure explained 76% of the variance. The correlation between cognitive function as measured by the MMSE and ability to communicate as measured with HCS was found to be moderate for those with an MMSE score of 0–10 (−0.61) and low for persons with an MMSE score of 11–20 (−0.06). CONCLUSIONS: The HCS is a reliable and valid scale for assessing communication ability in persons with moderate and severe cognitive impairment, and might have a 1-factor or 3-factor structure.